Optimization and Development of Packaging in the Production of Aren Sugar (Arenga Pinnata Merr.) as a Superior Product of Kemang Village - Asep Rismunandar; Regis Al Farsy; Gessica Audina Prahesti; Fadhia Nabila Safitri; Salsha Puspita Rahayu; Rizka Triani Fuziawati (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Kemang village in the Bojongpicung District, Cianjur Regency, has natural potential in the form of aren trees that produce sap with a sugar content of 10–15%, which is then processed into ant sugar in the form of yellowish-brown powder. However, the ant sugar products from this village still face challenges in packaging due to the limited knowledge and technology among local producers. This research aims to optimize the production process up to packaging and develop packaging innovations to enhance product quality. With a descriptive qualitative field research approach, direct observations were made of the production process at BUMDesa Kemang. The result is a new packaging that is more informative, visually appealing, and uses aluminum foil in accordance with SNI 0957:2017, which can protect the product from light, air, and moisture, thereby maintaining quality and extending the product's shelf life.